The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG). Issue 1 (1st January 2015) - Chen, Robert T.; Carbery, Baevin; Mac, Lisa; Berns, Kenneth I.; Chapman, Louisa; Condit, Richard C.; Excler, Jean-Louis; Gurwith, Marc; Hendry, Michael; Khan, Arifa S.; Khuri-Bulos, Najwa; Klug, Bettina; et al.
Abstract: Recombinant viral vectors provide an effective means for heterologous antigen expression in vivo and thus represent promising platforms for developing novel vaccines against human pathogens from Ebola to tuberculosis. An increasing number of candidate viral vector vaccines are entering human clinical trials. The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) was formed to improve our ability to anticipate potential safety issues and meaningfully assess or interpret safety data, thereby facilitating greater public acceptance when licensed.